Discourses on gender and sexual inequality the legacy of Sandra L. Bem - Kohlman, Marla H., editor; Krieg, Dana B., editor (Bingley, UK Emerald Publishing Limited, 2017)
Publisher's Summary Discourses on Gender and Sexual Inequality: The Legacy of Sandra L. Bem focuses on emerging discourses on gender, gender roles, and gender schemas. This collection of essays aims to honor the legacy of Sandra Lipsitz Bem and, particularly, her trail-blazing text, The Lenses of Gender: Transforming the Debate on Sexual Inequality. Long before the terms transgender and cisgender were introduced into mainstream, academic, and activist discourses on gender, Bem was busy interrogating the use of gender as an essential organizing principle in society.Chapters in this volume aim to draw attention to the significance of Bem's research for current debates on gender and gender roles in the social sciences, questioning the ways in which the institution of gender has been, and remains, deeply contested. Contributors examine lived experiences of individuals influenced by institutional constructions of gender and examine practical aspects of gender from the perspectives of social policy. (source: Nielsen Book Data)9781787431973 20171204
Includes bibliographical references and index.
Keywords: Bem, Sandra L; Bem, Sandra L. -- Lenses of gender; Sex role; Sex discrimination; Equality; Gender identity